Quadriceps muscle reaction time in obese children - Guzman-Munoz, Eduardo; Mendez-Rebolledo, Guillermo; Sazo-Rodriguez, Sergio; Salazar-Mendez, Joaquin; Valdes-Badilla, Pablo; Nuñez Espinosa, Cristian Andrés; Herrera-Valenzuela, Tomas (My University, 2024)
This study aimed to determine the influence of obesity, according to body mass index (BMI) and fat mass percentage, on quadriceps muscle reaction times. The study utilized a cross-sectional design. The sample size consisted of 42 schoolchildren (54.5% girls) aged 11 to 12 years old. Participant measurements included weight and height, which were used to categorize individuals based on BMI. Additionally, the electrical bioimpedance technique was employed to categorize participants based on their body fat percentage. A sudden destabilization test of the lower limb was performed to assess the reaction time of the rectus femoris, vastus medialis, and vastus lateralis muscles. The results show that overweight/obese children have a longer muscle reaction time for both the rectus femoris (13 = 18.13; p = 0.048) and the vastus lateralis (13 = 14.51; p = 0.042). Likewise, when the children were classified by percentage of body fat the results showed that overfat/obese children have a longer muscle reaction time for both the rectus femoris (13 = 18.13; p = 0.048) and the vastus lateralis (13 = 14.51; p = 0.042). Our results indicate that BMI and fat mass classification negativity alter the muscle reaction time in children. Overweight/obese or overfat/obese children showed longer reaction times in the rectus femoris and vastus lateralis muscles compared to children with normal weight. Based on these findings, it is suggested that in overweight and obese children, efforts not only focus on reducing body weight but that be complemented with training and/or rehabilitation programs that focus on preserving the normal physiological function of the musculoskeletal system.
Keywords: quadriceps; electromyography; childhood obesity; body fat; body mass index